2021
DOI: 10.1186/s12891-021-04715-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel predictive model and web calculator for evaluating transfusion risk after spinal fusion for spinal tuberculosis: a retrospective cohort study

Abstract: Objectives The incidence and adverse events of postoperative blood transfusion in spinal tuberculosis (TB) have attracted increasing attention. Our purpose was to develop a prediction model to evaluate blood transfusion risk after spinal fusion (SF) for spinal TB. Methods Nomogram and machine learning algorithms, support vector machine (SVM), decision tree (DT), multilayer perceptron (MLP), Naive Bayesian (NB), k-nearest neighbors (K-NN) and random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…The high C-index was especially suitable for wide use in large sample data [ 21 ]. The nomogram in the present study achieved the best discriminatory ability with an AUC of 0.785, which was slightly higher than that of the previously established nomogram (AUC = 0.75) [ 16 ].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The high C-index was especially suitable for wide use in large sample data [ 21 ]. The nomogram in the present study achieved the best discriminatory ability with an AUC of 0.785, which was slightly higher than that of the previously established nomogram (AUC = 0.75) [ 16 ].…”
Section: Discussioncontrasting
confidence: 74%
“…The requirement for blood transfusion in spinal tuberculosis surgery depends on several factors such as anaemia caused due to a deficiency of iron [ 11 ], vitamin B12, and folic acid [ 12 ], which are used to compound haemoglobin (HGB) and sex of the patient [ 13 15 ]. Dong et al exhibited that the factors such as preoperative mean corpuscular haemoglobin concentration, surgical duration, preoperative HGB, intraoperative blood loss, number of fused vertebrae, and anticoagulant history can predict the risk of blood transfusion after spinal tuberculosis fusion [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms can generate individual probabilities of clinical events by integrating different outcome and predictor variables and merging biological information with clinical prediction models ( 33 35 ). In recent years, it has been widely used as a prediction method in clinical settings ( 36 , 37 ), and it plays a role in promoting personalized medicine ( 38 , 39 ) and facilitates physicians in predicting disease risk ( 40 ). There have been many studies on CAS prevalence and risk factors ( 4 , 41 ), but few studies on CAS risk-prediction models have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, the use of a single radiographic indicator to assess the status of ACL had great uncertainty, while a model constructed using multiple indicators could greatly improve the accuracy. At present, there have been many models with multiple indicators showing high predictive accuracy in other fields [ 36 38 ]. As far as we knew, this was the first study combining multiple imaging indicators to construct an ACLD prediction model.…”
Section: Discussionmentioning
confidence: 99%